The Ecosystem Approach To Fisheries - Bianchi, Gabriella (CABI, 2014)
This book presents edited contributions to the Conference on Implementing the Ecosystem Approach to Fisheries, organized by the Nordic Council of Ministers and the Governments of Iceland and Norway, with technical support of the Food and Agriculture Organization (FAO) of the United Nations, held in Bergen, Norway from 26 to 28 September 2006. Considered as a follow-up to the 2001 Conference on Responsible Fisheries in the Marine Ecosystem, organized jointly by Iceland and the FAO, and with the co-sponsorship of Norway, the Bergen Conference aimed at reviewing concepts and addressing implementation issues related to applying the ecosystem approach to fisheries. Furthermore, experiences made and constraints encountered so far could be exchanged, including strategies and best practices that will facilitate further implementation in practical fisheries management.